BEHAVIORAL FACTORS INFLUENCING VARIABILITY OF ROOST COUNTS FOR RIO GRANDE TURKEYS - David M. Smith (Wildlife Society Bulletin)
Abstract Small winter flocks of Rio Grande turkeys (Meleagris gallopavo intermedia) used many more satellite roosts than did larger flocks on the Welder Wildlife Refuge in south Texas. Small flocks were more wary and had a wider choice of sites large enough to accommodate their entire group than the larger flocks. Winter flock size decreased, but not in proportion to the population decline. Roost counts were not reliable population estimators from December through February.